Refractory immune thrombocytopenic purpura associated with IgM monoclonal gammopathy of undetermined significance: Successful treatment with tirabrutinib plus conventional therapies. Issue 2 (17th March 2022) - Naka, Ryosuke; Kaneko, Hitomi; Nagata, Osamu; Tada, Kohei; Tashima, Masaharu; Mizutani, Chisato; Imada, Kazunori
Abstract: When immune thrombocytopenia (ITP) is secondary to malignant diseases, chemotherapy is expected to improve the platelet count (PC) as well. Herein, we report a case of a 72‐year‐old man with ITP refractory to standard therapies. IgM monoclonal gammopathy of undetermined significance (MGUS) was determined as an underlying disease. After bendamustine and rituximab (BR) therapy was found inadequately effective, tirabrutinib, a novel Bruton's tyrosine kinase inhibitor, was initiated, and the PC normalised subsequently. Surveillance of underlying diseases with which effective therapies are available may help manage refractory ITP, and IgM‐MGUS is potentially a targetable underlying disease with this newly available drug.